Understanding Differences between Equal Public Governance Models - Mirko Pečarič (Central European Public Administration Review)
Public administrations try to address changes in societies with various styles through various reforms based on different governance models, which are frequently transformed into domestic frames regardless of local specifics. The need for a tool with which the ideal types of governance models could be accommodated with national goals is, in times of increasing complexity, more and more relevant. As data as such are produced through numerous predispositions, the article proposes Ashby’s variety to capture the latter, through which it is possible to get closer to a successful administration of goals. On the other hand, Douglas’s grid and group model, Miles et al.’s organisational strategy, structure and process, and Hofstede’s cultural dimensions are used for the identification of needs. Even though public bodies are aware of the impact that culture/values has/have on models of public administration, countries base their decisions on it/them only indirectly. This article emphasises that certain values should be directly included in the governance models in accordance with their cultural backgrounds. The latter are always present in decisions’ predispositions (from which decisions obtain their frames and weights), and a successful administrator should not disregard them.